ZigZag transform with Durstenfeld shuffle for fast and secure image encryption - Erdal Güvenoğlu; Volkan Tunalı (Connection Science)
In this study, we propose an image encryption algorithm based on ZigZag transform with Durstenfeld Shuffling Algorithm (DSA), where we adopt confusion–diffusion architecture. Our encryption method is simpler to implement than high-dimensional chaos-based approaches, and its computational complexity is very low, which make it very fast and suitable for real-world applications. Additionally, its dependence on plaintext image makes it adaptive and hence very robust against brute force and differential attacks. Experimental analyses using histogram, correlation, NIST, NPCR, UACI and PSNR values suggest that our proposed algorithm is strong and secure against statistical and differential attacks.